The Potency of Oral L-Arginine Suplementation Based on Chitosan-Coated Gold Nanoparticles (c-AuNPs) as Preeclampsia Prevention in Pregnant Women - Syafira, Fara; Deanasa, Raehan Satya Deanasa; Afladhanti, Putri Mahirah Afladhanti (SCRIPTA SCORE Scientific Medical Journal, 2022)
Preeclampsia is a multi-systemic hypertensive disorder in pregnant women after two weeks of gestation and can cause complications in about 6-10% of all pregnancies. The incidence of preeclampsia in Indonesia is 128,273/year or about 5.3%. However, the handling of preeclampsia in Indonesia is still not optimal. This disease is difficult to detect and often appears suddenly, so prevention efforts need to be taken as an essential step in reducing morbidity and mortality due to this disease. Previous studies have shown that L-Arginine exhibits potential properties in preventing preeclampsia. This literature review aims to determine the potential for oral L-Arginine supplementation to prevent preeclampsia in pregnant women. Search for literature using search engines such as Google Scholar, Science Direct, ResearchGate, and NCBI. Inclusion and exclusion criteria are used to eliminate unrelated journals so 38 journals are obtained. L-Arginine has great potential as a preventive supplementation of preeclampsia by increasing the vascular NO synthesis where NO deficiency in pregnant women can induce changes in the uteroplacental structure. Supplementation of the dietary L-Arginine at a low dose of 3 g/day for three to four weeks is required in early pregnancy. The use of chitosan-coated gold nanoparticles (c-AuNPs) as encapsulation on a protein increases the bioavailability of oral supplementation and improves the patient's clinical state. Further research regarding the effectiveness of L-Arginine supplementation orally with c-AuNPs and the optimal dosage as a preeclampsia preventive supplement is needed.